Mechanisms of Agricultural Land Transfer Influence on the Urban Settlement Intention of Rural Floating Population in China - Yu Xie; Yin Yao; Bingbing Zhang; Xiongying Chen; Xinyu Wang; Tsang-Kai Hung; Zijun Wang (Discrete Dynamics in Nature and Society)
In order to promote the citizenship of China’s rural floating population and improve the level of new urbanization, as an important source of property income for rural floating population, the transfer of agricultural land or not has an important impact on whether they choose to return to their hometowns or settle in cities. Based on data from the 2017 China Migrants Dynamic Survey (CMDS), this paper explores the mechanism of the impact of agricultural land transfer on the urban settlement intention of rural floating population by constructing a structural equation modeling and bootstrap test. The results show that agricultural land transfer has a significant positive impact on the urban settlement intention of rural floating population, with occupational prestige and identity recognition playing a part in mediating the effect. Actively promoting the identification and orderly transfer of agricultural land rights, improving the quality of urban employment for rural floating population by strengthening vocational skills training, and accelerating the equalization of urban public services to enhance the identity recognition of rural floating population are important in promoting the orderly and effective integration of rural floating population into cities and their genuine citizenship.